Smartphone apps commonly used by doctors working in Orthopaedic surgery at the University of the Witwatersrand in Johannesburg: Are they pee-reviewd? - Singh, Dr Virsen (My University, 2019)
Background: As the popularity of smartphones soar throughout the world, their usefulness within the workplace, and particularly the healthcare sector, has increased dramatically. Unfortunately, not all healthcare-related smartphone apps can be trusted in terms of the accuracy of their content. Just as articles in journals undergo a peer-review process to determine their accuracy, the medical world has begun to peer-review the contents of medical apps. In this study, we aim to determine the most commonly used orthopaedic smartphone apps in our population group as well as find out if the content of these apps has been peer-reviewed. Methods: A prospective study was conducted in the Department of Orthopaedic Surgery at the University of the Witwatersrand, to determine the most commonly used healthcare-related apps. We then analysed the content of these apps, to see if it was peer-reviewed. Results: Of the 87 doctors surveyed (22 consultants; 49 registrars and 10 medical officers), 81 used their smartphones in their medical practice. The majority of doctors used apps which fell into the “reference” category, which allowed them to quickly access information regarding diagnosis, treatment and surgical approaches. Only seven doctors (8%) had checked to see if the apps they were using had been peer-reviewed. Twelve doctors (14%) felt that it was not important to peer-review these apps, while the majority (68 doctors, 78%) felt that it was important, but had not specifically checked. Discussion: Regarding the content of the apps, only eight of the thirteen apps included in the survey (62%) had been peer-reviewed by an expert in the field of orthopaedic surgery. The other five apps (38%) had never been reviewed in terms of their content. Some of the apps did not even have a medical expert on their development team. Conclusion: Our recommendation is that apps intended for use by clinicians should all undergo a peer-review process before being made available for download. Furthermore, these apps should provide a concise summary of the development process in the app description, which the user can peruse before downloading and using the app. Lastly, we believe that the onus lies with the clinician to ensure the accuracy of the content of these apps before using them in the healthcare setting.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Medicine Johannesburg, 2019